2017
DOI: 10.1080/03069885.2017.1285006
|View full text |Cite
|
Sign up to set email alerts
|

Applying phenomenography in guidance and counselling research

Abstract: Jaana Kettunen is a researcher at the Finnish Institute for Educational Research of the University of Jyväskylä. Her research focuses on social media in career services. Recently she has also studied the ethical practice in social networking and the role of ICT in relation to national lifelong guidance policies. Päivi Tynjälä Applying Phenomenography in Guidance and Counselling ResearchThis paper examines phenomenography as a viable qualitative approach in guidance and counselling research. A phenomenographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 42 publications
0
49
0
3
Order By: Relevance
“…In qualitative research, the quality of the data and the variation of respondents is a bigger concern than the quantity of the data. Some researchers have reported very small saturation point, that is, the point where no new information emerges when the number of participants is increased (Kettunen and Tynjälä 2018). We believe that in our study the experts interviewed and our analysis provided a useful basis for further, quantitative, investigation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In qualitative research, the quality of the data and the variation of respondents is a bigger concern than the quantity of the data. Some researchers have reported very small saturation point, that is, the point where no new information emerges when the number of participants is increased (Kettunen and Tynjälä 2018). We believe that in our study the experts interviewed and our analysis provided a useful basis for further, quantitative, investigation.…”
Section: Discussionmentioning
confidence: 96%
“…The purpose was to collaboratively produce the categories. This kind of group approach to data analysis makes it less likely that the analysis will stop partway (Bowden 2000; Kettunen and Tynjälä 2018). The final results reported here are thus based on researcher triangulation approach.…”
Section: Collection Of the Data And Analytic Methodsmentioning
confidence: 99%
“…Here, the group process helped to ensure the completeness of the analysis. Furthermore, it helped minimize each researcher's personal perspective to remain true to the data in formulating the categories of description (Kettunen & Tynjälä, 2018). After preliminary categories were decided, these were discussed and finally agreed on after some negotiations regarding interpretations.…”
Section: Rigor Reliability and Validitymentioning
confidence: 99%
“…Finally, the findings of this research depend on the context (higher education of Bangladesh), which is in line with the phenomenographic research approach. Kettunen and Tynjälä (2018) reported that "qualitative studies' findings are unique in their respective contexts; nonetheless, transferability to other settings and groups may be possible" (p. 7). Therefore, the students' conceptions of mobile learning, which were discerned in this research, may be useful for similar contexts in other countries in a global perspective.…”
Section: Limitation and Conclusionmentioning
confidence: 99%
“…Ma r t o n [ 24 ] d es c r i b e s phenomenography as an empirical study of the diverse ways in which people experience and apprehend various phenomena. Since the early 2000s, its use as a research method has broadened from education into a wider range of topic areas, such as mental health [25], information literacy [26] and counselling [27], where the purpose of the research is to understand the diverse ways in which groups of people experience phenomena. It is not a method that is apparent in information technology (IT) literature; research into user perceptions of IT has tended to concentrate upon methods that attempt to find consensus or majority views that relate to ease of use and usefulness of technology, such as the Technology Acceptance Model [28].…”
Section: Phenomenographic Methods For Evaluating Virtual Aveburymentioning
confidence: 99%